Phytochemical composition, Antioxidant and Anti-inflammatory potential of bioactive fractions from extracts of three medicinal plants traditionally used to treat liver diseases in Burkina Faso. - K. Konaté; A. Souza; Kassi Yomalan Thérèse; I. C. Dibala; Nicolas Barro; J. MillogoRasolodimby; O. G. Nacoulma (International Journal of Phytomedicine, 2011)
Our aim in this study concerning the ethyl acetate and dichloromethane fractions was to provide a scientific basis for the treatment of hepatitis B in Burkina Faso of these three ethnomedicinal plants. As a result, we evaluated polyphenol content, antioxidant and anti-inflammatory evaluated by lipoxygenase (LOX) inhibitory and Xanthine Oxidase (XO) activities of aqueous acetone bioactive fractions from three species of Malvaceae (Sida cordifolia, Sida rhombifolia, S. urens). Folinciocalteu; AlCl3 methods and tannic acid respectively were used for polyphenol content research. The antioxidant activity of the samples was evaluate using three separate methods, inhibition of free radical 2,2-diphenyl-1-picrylhydramzyl (DPPH), ABTS radical cation decolorization assay, Iron (III) to iron (II) reduction activity (FRAP). For anti-inflammatoty activity, lypoxygenase and xanthine oxidase inhibitory activities were used. Finally, in this study, the ethyl acetate fraction has shown the best results comparatively to the dichloromethane fraction.